Smallholder farms have and can store more carbon than previously estimated. Issue 6 (15th December 2022) - Ewing, Patrick M.; Tu, Xinyi; Runck, Bryan C.; Nord, Alison; Chikowo, Regis; Snapp, Sieglinde S.
Abstract: Increasing soil organic carbon (SOC) stocks is increasingly targeted as a key strategy in climate change mitigation and improved ecosystem resiliency. Agricultural land, a dominant global land use, provides substantial challenges and opportunities for global carbon sequestration. Despite this, global estimates of soil carbon sequestration potential often exclude agricultural land and estimates are coarse for regions in the Global South. To address these discrepancies and improve estimates, we develop a hybrid, data‐augmented database approach to better estimate the magnitude of SOC sequestration potential of agricultural soils. With high‐resolution (30 m) soil maps of Africa developed by the International Soils Database (iSDA) and Malawi as a case study, we create a national adjustment using site‐specific soil data retrieved from 1160 agricultural fields. We use a benchmark approach to estimate the amount of SOC Malawian agricultural soils can sequester, accounting for edaphic and climatic conditions, and calculate the resulting carbon gap. Field measurements of SOC stocks and sequestration potentials were consistently larger than iSDA predictions, with an average carbon gap of 4.42 ± 0.23 Mg C ha −1 to a depth of 20 cm, with some areas exceeding 10 Mg C ha −1 . Augmenting iSDA predictions with field data also improved sensitivity to identify areas with high SOC sequestration potential by 6%—areas that may benefit from improved management practices. Overall, we estimate that 6.8 million ha of surface soil suitable for agriculture in Malawi has the potential to store 274 ± 14 Tg SOC. Our approach illustrates how ground truthing efforts remain essential to reduce errors in continent‐wide soil carbon predictions for local and regional use. This work begins efforts needed across regions to develop soil carbon benchmarks that inform policies and identify high‐impact areas in the effort to increase SOC globally. Abstract : We augmented a high‐resolution continental soils database with local data to develop hybrid, regional predictions of carbon stocks and then estimated carbon sequestration potential within agricultural soils. The method found that agricultural soils in Malawi can sequester 4.4 Mg C ha on average with a change in management, a 90% increase over database predictions alone, and the method better identified high sequestration locations. Results will aid policy and management interventions to improve food security and mitigate climate change.